2013
DOI: 10.1155/2013/729349
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Food Antigens in Patients with Autistic Spectrum Disorders

Abstract: Purpose. Immune system of some autistic patients could be abnormally triggered by gluten/casein assumption. The prevalence of antibodies to gliadin and milk proteins in autistic children with paired/impaired intestinal permeability and under dietary regimen either regular or restricted is reported. Methods. 162 ASDs and 44 healthy children were investigated for intestinal permeability, tissue-transglutaminase (tTG), anti-endomysium antibodies (EMA)-IgA, and total mucosal IgA to exclude celiac disease; HLA-DQ2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 38 publications
(69 reference statements)
2
47
1
4
Order By: Relevance
“…Children with autism have significantly higher levels of IgG AGA (but not IgA) compared with healthy controls, particularly those with gastrointestinal symptoms [23] . Recent studies confirmed these findings and also reported an increase in antibodies directed to several other food allergens, including casein and whole milk [24] .…”
Section: Gluten Sensitivity and Autismmentioning
confidence: 52%
“…Children with autism have significantly higher levels of IgG AGA (but not IgA) compared with healthy controls, particularly those with gastrointestinal symptoms [23] . Recent studies confirmed these findings and also reported an increase in antibodies directed to several other food allergens, including casein and whole milk [24] .…”
Section: Gluten Sensitivity and Autismmentioning
confidence: 52%
“…de Magistris et al (44) have provided one of the most comprehensive analysis of the leaky gut and autism so far based on their dataset looking at permeability measures for both children with autism and their extended family. Alongside other studies (45,46) evidence is accumulating to suggest that abnormal intestinal permeability is a finding for a proportion of people on the autism spectrum and may well be influenced by the implementation of a GFCF diet. Further questions are being asked about this area of investigation insofar as the nature of the permeability present and, as is noted in cases of CD, how tight-junction proteins may be implicated in this process.…”
Section: Increased Intestinal Permeabilitymentioning
confidence: 99%
“…Among psychiatric disorders, a minority (6%) of patients with NCGS showed a previous clinical history of eating behavior abnormalities, while autism spectrum disorders (ASD) have been hypothesized to be associated with NCGS [47,48]. Notably, a gluten-and casein-free diet might have a positive effect in improving hyperactivity and mental confusion in some patients with ASD.…”
Section: Epidemiological and Clinical Picturementioning
confidence: 99%